Drivers and Implications of Combined Investment in Renewables and Energy Storage in the Residential Sector - Cho; Kim,Youngsoo; Murali,Karthik; Yavuz,Mesut (Decision Sciences, 2023)
Residential consumers are increasingly combining renewables with energy storage systems. However, changes in policies and support for these technologies may impact their adoption and the outlook for the energy industry. In this paper, we consider a grid-connected household's problem of determining the optimal capacities of these two technologies as well as the battery operating policy that minimizes its electricity costs when faced with time-of-use electricity prices and sellback credits. We identify the impact of household characteristics, technological progress, and electricity pricing policies on the levels of investment in these two technologies. Furthermore, we supplement our analytical results with a case study of two U.S. cities and identify policy guidelines for the design of a technology subsidy program aimed at stimulating the adoption of these technologies and the ensuing implications for residential customers, the environment, and grid reliability. Our paper has implications for several stakeholders in practice on (i) how the adoption of renewables is affected by energy storage (and vice versa) and (ii) how electricity pricing, technological progress, and subsidy policies can shape the adoption of both technologies.
Keywords: Supply Chain

Drivers and Implications of Combined Investment in Renewables and Energy Storage in the Residential Sector - Cho; Kim,Youngsoo; Murali,Karthik; Yavuz,Mesut (Decision Sciences, 2023)
Residential consumers are increasingly combining renewables with energy storage systems. However, changes in policies and support for these technologies may impact their adoption and the outlook for the energy industry. In this paper, we consider a grid-connected household's problem of determining the optimal capacities of these two technologies as well as the battery operating policy that minimizes its electricity costs when faced with time-of-use electricity prices and sellback credits. We identify the impact of household characteristics, technological progress, and electricity pricing policies on the levels of investment in these two technologies. Furthermore, we supplement our analytical results with a case study of two U.S. cities and identify policy guidelines for the design of a technology subsidy program aimed at stimulating the adoption of these technologies and the ensuing implications for residential customers, the environment, and grid reliability. Our paper has implications for several stakeholders in practice on (i) how the adoption of renewables is affected by energy storage (and vice versa) and (ii) how electricity pricing, technological progress, and subsidy policies can shape the adoption of both technologies.
Keywords: Supply Chain

The Impact of heterogeneity in consumer characteristics on the design of optimal time-of-use tariffs - Murali,Karthik; Choi,Dong Gu (Energy, 2022)
Unlike commercial and industrial sectors where they have been successfully deployed, the rollout of voluntary Time-of-Use (TOU) tariffs in the residential sector has been tepid. One cause for this limited penetration of TOU tariffs in the residential sector is the difficulty in offering appropriate price incentives to a consumer class that is heterogeneous in its demographics and preferences. In this paper, we develop a parsimonious game-theoretic model to shed light on the optimal pricing problem from the utility's perspective when its consumers vary in their electricity consumption scheduling preferences as well as their willingness or flexibility to shift consumption in response to price incentives offered by the utility. Using this model, we generate structural insights into the role of the two types of consumer heterogeneity on the design and potential of voluntary TOU tariffs. We also show how our model and insights can be used to evaluate the current state and potential of TOU tariffs in two U.S. states.
Keywords: Supply Chain

The Impact of heterogeneity in consumer characteristics on the design of optimal time-of-use tariffs - Murali,Karthik; Choi,Dong Gu (Energy, 2022)
Unlike commercial and industrial sectors where they have been successfully deployed, the rollout of voluntary Time-of-Use (TOU) tariffs in the residential sector has been tepid. One cause for this limited penetration of TOU tariffs in the residential sector is the difficulty in offering appropriate price incentives to a consumer class that is heterogeneous in its demographics and preferences. In this paper, we develop a parsimonious game-theoretic model to shed light on the optimal pricing problem from the utility's perspective when its consumers vary in their electricity consumption scheduling preferences as well as their willingness or flexibility to shift consumption in response to price incentives offered by the utility. Using this model, we generate structural insights into the role of the two types of consumer heterogeneity on the design and potential of voluntary TOU tariffs. We also show how our model and insights can be used to evaluate the current state and potential of TOU tariffs in two U.S. states.
Keywords: Supply Chain

Why have Voluntary Time-of-Use Tariffs Fallen Short in the Residential Sector? - Murali,Karthik; Choi,Dong Gu; Lim,Michael Kim; Thomas,Valerie (Production and Operations Management, 2020)
We investigate the causes behind the underwhelming adoption of voluntary Time-of-Use (TOU) tariffs in the residential electricity market. TOU tariffs are deployed by utilities to better match electricity generation capacity with market demand by giving consumers price incentives to reduce their consumption when electricity demand is at its peak. However, consumers in residential electricity markets are heterogeneous in their consumption preferences. Hence, utilities face a trade-off when deploying voluntary TOU tariffs---to provide aggressive price incentives that will only appeal to consumers with flatter profiles or milder incentives to appeal to a larger proportion of the market. Using a game-theoretic model, we identify the key factors that determine the viability of voluntary TOU tariff deployment. On the supply side, the gap between wholesale prices in the peak and off-peak periods determines how much the utility stands to benefit by inducing demand response. On the demand side, heterogeneity within target consumer sets determines how much demand response the utility can induce with a certain price incentive. We show that misaligned incentives between utilities and regulators lead to underwhelming TOU tariff adoption compared to the socially desirable level, and that this under-adoption is worse when consumption preferences are uniformly distributed. We also evaluate the degree of cross-subsidization across tariff structures to identify their implications for equity among the different consumer types, and find that low levels of voluntary TOU adoption are less equitable than the default tariffs.
Keywords: Supply Chain

The Effects of Ecolabels and Environmental Regulations on Green Product Development - Murali,Karthik; Lim,Michael Kim; Petruzzi,Nicholas C (Manufacturing and Service Operations Management, 2019)
Problem definition: We develop a framework for studying the impact of voluntary ecolabels and mandatory environmental regulation on green product development among competing firms. Academic/practical relevance: We contribute to the academic literature on environmental quality competition by explicitly accounting for the credibility of environmental claims made by firms, and by exploring the implications for society of two mechanisms used to remedy credibility-related consumer discounting of firms’ self-declared environmental qualities. We draw parallels between our findings and instances of environmental labeling and regulation from industry to highlight the practical implications of our study. Methodology: We use a game-theoretic framework to analyze a consumer-driven model of green product development. Results: Credibility asymmetry drives product differentiation between two competing firms. The less credible firm always adopts external certification, while the more credible firm does so only if its credibility is sufficiently low. Credibility may also determine whether or not the government should intervene. In the absence of an external certifier, the regulator should intervene by imposing a mandatory environmental standard that is decreasing in stringency as the credibility of the more credible firm increases. In the presence of a certifier, the regulator should intervene if neither firm is sufficiently credible, or if consumers do not value environmental stewardship highly. Managerial implications: We identify how and when government should (and should not) intervene to stimulate green product development when competing firms can use self-labels or external certifications to communicate their environmental performance to consumers. We also determine the optimal strategies for the competing firms and external certifiers.
Keywords: Supply Chain

The Effects of Ecolabels and Environmental Regulations on Green Product Development - Murali,Karthik; Lim,Michael Kim; Petruzzi,Nicholas C (Manufacturing and Service Operations Management, 2019)
Problem definition: We develop a framework for studying the impact of voluntary ecolabels and mandatory environmental regulation on green product development among competing firms. Academic/practical relevance: We contribute to the academic literature on environmental quality competition by explicitly accounting for the credibility of environmental claims made by firms, and by exploring the implications for society of two mechanisms used to remedy credibility-related consumer discounting of firms’ self-declared environmental qualities. We draw parallels between our findings and instances of environmental labeling and regulation from industry to highlight the practical implications of our study. Methodology: We use a game-theoretic framework to analyze a consumer-driven model of green product development. Results: Credibility asymmetry drives product differentiation between two competing firms. The less credible firm always adopts external certification, while the more credible firm does so only if its credibility is sufficiently low. Credibility may also determine whether or not the government should intervene. In the absence of an external certifier, the regulator should intervene by imposing a mandatory environmental standard that is decreasing in stringency as the credibility of the more credible firm increases. In the presence of a certifier, the regulator should intervene if neither firm is sufficiently credible, or if consumers do not value environmental stewardship highly. Managerial implications: We identify how and when government should (and should not) intervene to stimulate green product development when competing firms can use self-labels or external certifications to communicate their environmental performance to consumers. We also determine the optimal strategies for the competing firms and external certifiers.
Keywords: Supply Chain

Why have Voluntary Time-of-Use Tariffs Fallen Short in the Residential Sector? - Murali,Karthik; Choi,Dong Gu; Lim,Michael Kim; Thomas,Valerie (Production and Operations Management, 2019)
We investigate the causes behind the underwhelming adoption of voluntary Time-of-Use (TOU) tariffs in the residential electricity market. TOU tariffs are deployed by utilities to better match electricity generation capacity with market demand by giving consumers price incentives to reduce their consumption when electricity demand is at its peak. However, consumers in residential electricity markets are heterogeneous in their consumption preferences. Hence, utilities face a trade-off when deploying voluntary TOU tariffs---to provide aggressive price incentives that will only appeal to consumers with flatter profiles or milder incentives to appeal to a larger proportion of the market. Using a game-theoretic model, we identify the key factors that determine the viability of voluntary TOU tariff deployment. On the supply side, the gap between wholesale prices in the peak and off-peak periods determines how much the utility stands to benefit by inducing demand response. On the demand side, heterogeneity within target consumer sets determines how much demand response the utility can induce with a certain price incentive. We show that misaligned incentives between utilities and regulators lead to underwhelming TOU tariff adoption compared to the socially desirable level, and that this under-adoption is worse when consumption preferences are uniformly distributed. We also evaluate the degree of cross-subsidization across tariff structures to identify their implications for equity among the different consumer types, and find that low levels of voluntary TOU adoption are less equitable than the default tariffs.
Keywords: Supply Chain

Municipal Groundwater Management: Optimal Allocation and Control of a Renewable Natural Resource - Murali,Karthik; Lim,Michael Kim; Petruzzi,Nicholas C (Production and Operations Management, 2015)
We study a municipal groundwater management problem to determine optimal allocation and control policies in the presence of water transfer opportunities. We establish and characterize threshold polices governing export or import decisions of a given municipality. In the spirit of the Triple Bottom Line (3BL), we ascertain that exporting (importing) water through a water market defined by an exogenous export/import price is detrimental (beneficial) to both society and the environment within the municipality. In contrast, fixed quantity trading between two municipalities defined by an endogenously negotiated export/import price can have positive as well as negative impacts from a global 3BL perspective. In particular, typical trading scenarios that occur between municipalities can be detrimental to the environment. We also study the implications of privatization, and find that a privatized municipality would be more (less) likely to export (import) water as compared to its non‐privatized counterpart, resulting in negative implications for society within the municipality. However, if exports are banned, privatization can benefit the environment by mitigating the damage caused by the extraction differential, a phenomenon analogous to the green paradox. Moreover, careful and restricted privatization of municipalities can lead to positive global 3BL impacts from fixed quantity trading.
Keywords: Supply Chain

Municipal Groundwater Management: Optimal Allocation and Control of a Renewable Natural Resource - Murali,Karthik; Lim,Michael Kim; Petruzzi,Nicholas C (Production and Operations Management, 2015)
We study a municipal groundwater management problem to determine optimal allocation and control policies in the presence of water transfer opportunities. We establish and characterize threshold polices governing export or import decisions of a given municipality. In the spirit of the Triple Bottom Line (3BL), we ascertain that exporting (importing) water through a water market defined by an exogenous export/import price is detrimental (beneficial) to both society and the environment within the municipality. In contrast, fixed quantity trading between two municipalities defined by an endogenously negotiated export/import price can have positive as well as negative impacts from a global 3BL perspective. In particular, typical trading scenarios that occur between municipalities can be detrimental to the environment. We also study the implications of privatization, and find that a privatized municipality would be more (less) likely to export (import) water as compared to its non‐privatized counterpart, resulting in negative implications for society within the municipality. However, if exports are banned, privatization can benefit the environment by mitigating the damage caused by the extraction differential, a phenomenon analogous to the green paradox. Moreover, careful and restricted privatization of municipalities can lead to positive global 3BL impacts from fixed quantity trading.
Keywords: Supply Chain

Informal Cross-Border Trade in Africa: Operations, Policy, and Opportunities - Park,Jimin; Lim,Michael K; Murali,Karthik (Management Science)
Informal cross-border trade (ICBT) refers to the illegal activities of cross-border commerce conducted by unregistered small-scale traders. We seek to develop insights to understand the ICBT value chain and offer policy recommendations to successfully integrate it into the formal economy. Using a game-theoretic model, we analyze the operations and key market dynamics of ICBT. We analyze the policy implications of three representative UN directives: enhancing marginalized traders' access to formal channels, reducing export tax rates for formal traders, and introducing an alternative simplified trade regime (STR) for informal traders. All three policies result in an increase in government proceeds when the inherent profitability of the formal or STR channels is sufficiently high. Furthermore, social welfare increases when the policies effectively balance wholesale price competition within the formal and informal channels. We apply our model to a case study based on Uganda's agricultural exports over an 11-year horizon. The access enhancement policy is most effective in increasing government proceeds but least effective in improving the welfare of other participants. The tax reduction policy enhances traders' profitability but sacrifices the welfare of farmers and government proceeds substantially. Finally, the STR acknowledgement policy results in the largest increase in profitability of marginalized traders and farmers but comes at the cost of government proceeds.
Keywords: Supply Chain